An exploration of the leadership strategies of Facebook community leaders - Tali Gazit; Jenny Bronstein (Online Information Review, 2020)
Purpose Understanding leadership in newly created online social spaces, such Facebook communities, is an important new area of study within leadership research. This study explores an existing leadership model in offline environments by analyzing leadership strategies used by Facebook community leaders. Design/methodology/approach By using both quantitative and qualitative methods, data were collected through a survey from 94 Facebook community leaders about their leadership strategies. Findings Findings show that the framework of leadership behavior in offline groups can also be observed in Facebook communities. The content analysis of the open-ended questions reveals new categories reflecting unique leadership strategies in online environments. Leaders that participated in the study focused on strategies of content and team management, provided their groups with relevant content and personal stories to engage their members and strived to lead both offline and online-related social spaces to build a sense of community. Originality/value The growing number of Facebook community leaders and their key role in social media communities raise new questions about their position in light of what is already known about traditional leadership. Since social media occupies a central place in almost every aspect in everyday life, understanding the way that leaders manage these online communities is ever more important, and it can lead to an advancement in online communications. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/OIR-01-2020-0034 .